2014
DOI: 10.3163/1536-5050.102.1.011
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the care navigation model: potential roles for health sciences librarians

Abstract: This study analyzed the overlap between roles and activities that health care navigators perform and competencies identified by the Medical Library Association’s (MLA’s) educational policy statement.Roles and activities that health care navigators perform were gleaned from published literature. Once common roles and activities that health care navigators perform were identified, MLA competencies were mapped against those roles and activities to identify areas of overlap. The greatest extent of correspondence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Additionally, the qualitative content analysis employed in this paper comes to many of the same conclusions as those methods reviewed earlier in chapter two: medical health and information specialists have the ability to rise to the demands placed on medical libraries, medical facilities, and libraries in general, armed with an array of informative resources. The data certainly highlight what Huber et al (2014) point out, which is that both the library science and medical fields clearly overlap. The collaboration is evident by the very fact that the MLA, an organization for medical librarians, included such a thorough COVID-19 resource guide for medical workers and librarians alike.…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, the qualitative content analysis employed in this paper comes to many of the same conclusions as those methods reviewed earlier in chapter two: medical health and information specialists have the ability to rise to the demands placed on medical libraries, medical facilities, and libraries in general, armed with an array of informative resources. The data certainly highlight what Huber et al (2014) point out, which is that both the library science and medical fields clearly overlap. The collaboration is evident by the very fact that the MLA, an organization for medical librarians, included such a thorough COVID-19 resource guide for medical workers and librarians alike.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, a new approach to expanding medical libraries or patient education centers is needed. For example, Huber and colleagues proposed expanding a patient navigator program by including library and information science professionals who are “tasked with the selection and dissemination of understandable, relevant, culturally appropriate information.” Likewise, medical librarians could work with PHR teams or patient navigator teams to help solicit relevant personal health documents from patients, perform as mediated searchers, and train users of PHR systems [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their task of guiding patients through the system, care navigators focus on the needs of individuals. Studies in the cancer care setting have shown the benefits of care navigators [9-11]. However, despite having a positive effect on patients’ satisfaction, quality of life, and functionality [7,12], the high cost of care navigators remains a barrier to their wider employment [13].…”
Section: Introductionmentioning
confidence: 99%